2021
DOI: 10.5271/sjweh.3947
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of low-back outcomes and alternative measures of cumulative external and internal vibration load on the lumbar spine of professional drivers

Abstract: A prospective cohort study of low-back outcomes and alternative measures of cumulative external and internal vibration load on the lumbar spine of professional drivers by Bovenzi M, Schust M This is the first epidemiological study with a prospective cohort design that investigates the relationship of low-back outcomes to cumulative exposure to whole-body vibration assessed in terms of force-based internal load on the lumbar spine of professional drivers. Internal lumbar forces were calculated by means of anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In addition, a study conducted by Bovenzi [16,48] analysed the occurrence of low back symptoms in professional drivers over a two-year period. The study showed a significant association between low back symptoms (low back pain, sciatica) and measures of internal lumbar load (S A d and Factor R A in particular).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study conducted by Bovenzi [16,48] analysed the occurrence of low back symptoms in professional drivers over a two-year period. The study showed a significant association between low back symptoms (low back pain, sciatica) and measures of internal lumbar load (S A d and Factor R A in particular).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have evidenced a relationship between long-term exposure to WBV and the occurrence of musculoskeletal disorders (MSDs), such as low back pain [14][15][16], sciatica [17], neck pain [18,19], degenerative changes in the lumbar spine [20], and other disorders such as cognitive/motor impairment. In fact, Costa et al [21] found evidence of cognitive/motor impairment as a result of WBV exposure.…”
Section: Introductionmentioning
confidence: 99%
“…De la Hoz-Torres et al [38] assessed the short-term WBV exposure transmitted to drivers of heavy equipment vehicles (HEVs) and found that the VDV method was more restrictive for exposure levels above the limiting values, whereas other short-term assessment methods indicated that the same exposure levels were safe for workers. In addition, a recent study conducted by Bovenzi and Schust [19] concluded that assessment methods based on measures of external vibration acceleration provided worse predictors of LBP than measures of internal lumbar forces.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies suggest that these methods may underestimate the severity of the effects of exposure to vibration containing shocks [18]. Recent research has revealed that there is an elevated risk of MSDs related to LBP, even for WBV exposures that are below the limits set in the European directive [19]. Moreover, the effects of long-term WBV exposure are not considered by the A (8) and VDV models, which may mean although that an exposure to WBV may be assessed as safe in the short term, it may have adverse consequences for the worker's health in the long term [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation